Neonatal Hyperbilirubinemia and Neurodevelopmental Delay Assessment at Six Months of Age - Hassan Boskabadi; Javad Akhondian; Ali Taghipour; Narges Hashemi; Mahla Esmaeilzadeh; Reza Nejad Shahrokh Abadi (Mashhad University of Medical Sciences, 2023)
Background: Being toxic to the developing central nervous system, hyperbilirubinemia may cause neurological damage or developmental delay. This study aimed to assess the relationship between hyperbilirubinemia and developmental delay at six months of age in infants with neonatal severe hyperbilirubinemia.Methods: A prospective cohort study was conducted on infants with a gestational age of >35 weeks and hyperbilirubinemia from 2014 to 2020. The neurodevelopmental assessment was performed using the Denver Developmental Screening Test II (DAS II). The collected data were statistically analyzed by SPSS software (version 26).Results: Among the three main causes of hyperbilirubinemia, 9.6% of the neonates had blood group incompatibility; ABO, Rh, and ABO +Rh were observed in 7.5%, 1.6%, and 1.1% of the neonates, respectively, and 1.1% of the infants were diagnosed with glucose-6-phosphate dehydrogenase deficiency.  The correlation between hyperbilirubinemia and developmental delay in all four domains according to the DAS II test was statistically significant (P<0.001). Moreover, the severity of hyperbilirubinemia was proved to have a positive correlation with the severity of the developmental delay. Furthermore, this study found a significant correlation (P<0.001) between the causes of icterus and the probability of neurodevelopmental delay at six months of age (Correlation Coefficient=0.470, sig=0.000).Conclusion: There is a strong correlation between hyperbilirubinemia and developmental delay at six months of age in infants with neonatal hyperbilirubinemia. The severity of hyperbilirubinemia is significantly associated with the cause of jaundice. It is also demonstrated that the severity of hyperbilirubinemia has a positive correlation with the severity of the developmental delay.